Evaluating the Effectiveness of Biodiverse Green Schoolyards on Child BMI z-Score and Physical Metrics: A Pilot Quasi-Experimental Study - Bo H. W. van Engelen; Lore Verheyen; Bjorn Winkens; Michelle Plusquin; Onno C. P. van Schayck (Children, 2025)
Background: Childhood obesity is a significant public health issue linked to poor diet, low physical activity, and limited access to supportive environments. Green schoolyards may promote physical activity and improve health outcomes. This study evaluated the impact of the Green Healthy Primary School of the Future (GHPSF) intervention—greening schoolyards—on children’s BMI z-scores, waist circumference, and hip circumference over 18 months, and compared these effects to those observed in the earlier Healthy Primary School of the Future (HPSF) initiative. Methods: This longitudinal quasi-experimental study included two intervention and two control schools in Limburg, a province both in the Netherlands and Belgium. Children aged 8–12 years (n = 159) were assessed at baseline, 12 months, and 18 months for anthropometric outcomes. Linear mixed models were used to estimate intervention effects over time, adjusting for sex, age, country, and socioeconomic background. Standardized effect sizes (ESs) were calculated. Results: The intervention group showed a greater reduction in BMI z-scores at 12 months (ES = −0.15, p = 0.084), though this was not statistically significant. Waist circumference increased in both groups, but less so in the intervention group, at 12 months (ES = −0.23, p = 0.057) and 18 months (ES = −0.13, p = 0.235). Hip circumference and waist–hip ratio changes were minimal and non-significant. GHPSF effect sizes were comparable to or greater than those from the HPSF initiative. Conclusions: Though not statistically significant, trends suggest that greening schoolyards may support favorable changes in anthropometric outcomes. Further research with larger samples and longer follow-up is recommended.